2010
DOI: 10.1111/j.1467-839x.2010.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

System‐perpetuating asymmetries between explicit and implicit intergroup attitudes among indigenous and non‐indigenous Chileans

Abstract: The present research demonstrates a dissociation between explicit and implicit intergroup evaluation in the reciprocal attitudes between indigenous (Mapuche) and non‐indigenous Chileans. In both social groups, the explicit measures of attitudes towards the respective in‐group and out‐group were compared with the Implicit Association Test scores. The results indicate that the members of the low‐status minority might explicitly express a moderate evaluative preference for their in‐group but might implicitly deva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
0
19
0
4
Order By: Relevance
“…Sumado a esto, el fenotipo de los inmigrantes también se convierte en un factor de rechazo. La medición de actitudes implícitas en un grupo de chilenos muestra una preferencia por personas de color de piel clara, en comparación a personas de color oscuro (Uhlmann, Dasgupta, Elgueta, Greenwald & Swanson, 2002) o con rasgos Mapuche (Haye et al, 2010).…”
Section: Discussionunclassified
“…Sumado a esto, el fenotipo de los inmigrantes también se convierte en un factor de rechazo. La medición de actitudes implícitas en un grupo de chilenos muestra una preferencia por personas de color de piel clara, en comparación a personas de color oscuro (Uhlmann, Dasgupta, Elgueta, Greenwald & Swanson, 2002) o con rasgos Mapuche (Haye et al, 2010).…”
Section: Discussionunclassified
“…Mapuche participants, on the other hand, showed in-group favouritism at the explicit level and out-group favouritism at the implicit level. According to Haye et al ( 2010 ), the latter situation provides evidence of system-justifi cation tendencies among Mapuche respondents. Importantly, Mellor, Merino, Saiz, and Quilaqueo ( 2009 ) showed that Mapuche people report negative feelings, shame and powerlessness as a result of perceived discrimination.…”
Section: Ethnic Identities In Chilementioning
confidence: 92%
“…It has long been stated that minority groups sometimes internalise a sense of inferiority (Allport, 1954 ), particularly under low-status conditions (Jost & Banaji, 1994 ). Indeed, Haye et al ( 2010 ) found that non-indigenous Chileans expressed an evaluation of the Mapuche group equally positive to their in-group evaluation at the explicit level. However, they expressed a clear preference for their in-group at the implicit level.…”
Section: Ethnic Identities In Chilementioning
confidence: 94%
“…Investigating an adolescent sample in Cárdenas, Music, Contreras, Yeomans, and Calderón () showed that those who have high levels of subtle prejudice but low levels of blatant prejudice are still more likely to agree that we should “leave things as they are” regarding the rights of minority groups. Another study with Chilean adolescents showed that even though non‐indigenous Chileans show no in‐group preferences using explicit, self‐reported measures, they showed a consistent in‐group bias in their implicit attitudes (Haye et al., ).…”
Section: Studies On Peer Relations and Socioemotional Development In mentioning
confidence: 99%